COVID-19 and Power in Global Health - Amy Patterson; Mary A. Clark (Kerman University of Medical Sciences, 2020)
Political scientists bring important tools to the analysis of the coronavirus disease 2019 (COVID-19) pandemic, particularly a focus on the crucial role of power in global health politics. We delineate different kinds of power at play during the COVID-19 crisis, showing how a dearth of compulsory, institutional, and epistemic power undermined global cooperation and fueled the pandemic, with its significant loss to human life and huge economic toll. Through the pandemic response, productive and structural power became apparent, as issue frames stressing security and then preserving livelihoods overwhelmed public health and human rights considerations. Structural power rooted in economic inequalities between and within countries conditioned responses and shaped vulnerabilities, as the crisis threatened to deepen power imbalances along multiple lines. Calls for global health security will surely take on a new urgency in the aftermath of the pandemic and the forms of power delineated here will shape their outcome.